Strengthening institutions to accelerate growth and lower poverty - Ahmed, Sadiq; Alamgir, Mohiuddin, 1943-; Mujeri, Mustafa K.; Bangladesh Economists' Forum; Bangladesh Economists' Forum. Conference 2015 : Dhaka, Bangladesh) (Dhaka : Bangladesh Economists' Forum, 2016)
Outcome of the Second BEF Conference held in Dhaka in October 2015.
Includes bibliographical references (pages 121-126) and index.
Donated By Akbar Ali Khan
Keywords: Social institutions -- Bangladesh -- Congresses; Bangladesh -- Economic conditions -- 21st century -- Congresses; Bangladesh -- Economic policy -- 21st century -- Congresses